PENGATURAN DAN PELAKSANAAN PENGELOLAAN PERPARKIRAN KOTA - Indrati Rini (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
As one of local retribution’s sources, the handling of parking affair should be seriously concerned. Up till now, the regulations has not yet been implemented as expected There are still many regulation infractions by private sector and even by local government itself. Therefore, the office of parking affair should pay more attention and initiate more effective coordination among related offices, due to the achievement of local retributions revenue.